An Unusual Cause of Acute Cardiogenic Shock in the Operating Room. Issue 3 (11th January 2013) - Baptista, Rui; Fonseca, João; Marconi, Lorenzo; Furriel, Frederico; Prieto, David; Bento, Carlos; Antunes, Manuel J.; Figueiredo, Arnaldo
<x xml:space="preserve">Abstract</x> A 51‐year‐old man with a renal carcinoma with inferior vena cava (IVC) invasion was referred to our hospital for the performance of a radical nephrectomy with IVC thrombus excision. To prevent embolism, an IVC filter was implanted the day before surgery below the suprahepatic veins. On nephrectomy completion, the clinical status of the patient started to deteriorate and an unsuccessful attempt was made to excise the IVC thrombus. The patient developed profound refractory hypotension without significant bleeding and worsening splanchnic stasis was noted. A transesophageal echocardiogram was immediately performed in the operating room, revealing a hemispheric mass protruding from the IVC ostium to the right atrium, completely blocking all venous return. Volume depletion was evident by low left and right atrial volumes and increased septum mobility. No other abnormalities were found that could explain the shock, namely ventricular dysfunction or valvular disease. Cardiac surgery consultation was immediately obtained, ultimately deciding to perform a median sternotomy with direct exploration of right atrium. Under cardiopulmonary bypass, a 6‐cm long thrombotic mass was identified, involving the IVC filter, blocking all lower body venous return; the removal of the mass reversed the shock. The patient had an uneventful recovery. Adverse outcomes associated with IVC filters are common. Our case highlights the importance of a team approach to rapid changes in hemodynamic status in the operating room, including the surgeon, the anesthesiologist, and the cardiologist. It also emphasizes the pivotal role of transesophageal echocardiogram in the clinical evaluation of severely unstable patients.